2015
DOI: 10.17214/aot.43682
|View full text |Cite
|
Sign up to set email alerts
|

Oral mikroorganizmalara karşı propolisin antimikrobiyal etkinliği

Abstract: ÖZET GİRİŞPropolis çam, meşe, okaliptüs, kavak, kestane gibi ağaçlar ve bazı otsu bitkilerin tomurcuk, yaprak ve benzeri kısımlarından bal arıları tarafından toplanan ve mumla karıştırılarak kovan içerisinde birçok amaca yö-nelik olarak kullanılan zamk gibi yapışkan, reçinemsi, kokulu ve rengi koyu sarıdan kahverengiye kadar deği-şen bir maddedir. Arı bu maddeyi başı ile toraksı arasında bulunan bezlerden salgılamış olduğu aktif enzimlerle karıştırıp pelet haline getirir. Genel olarak, ham propolisin %50'sini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Metastatic infection due to bacterial displacement, metastatic damage caused by microbial toxins, and metastatic inflammation due to weak immune system can play a role in their pathogenesis. 25 Blod et al 26 reported that they detected several oral bacterial pathogens in the appendix lumens and suggested that the oral cavity may be a reservoir for AA. Aiyoshi et al 27 stated in their study that ectopic colonization of the appendix by oral Fusobacterium species may play an important role in the pathogenesis of AA.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic infection due to bacterial displacement, metastatic damage caused by microbial toxins, and metastatic inflammation due to weak immune system can play a role in their pathogenesis. 25 Blod et al 26 reported that they detected several oral bacterial pathogens in the appendix lumens and suggested that the oral cavity may be a reservoir for AA. Aiyoshi et al 27 stated in their study that ectopic colonization of the appendix by oral Fusobacterium species may play an important role in the pathogenesis of AA.…”
Section: Discussionmentioning
confidence: 99%